Why respiratory viruses or bacteria have the highest probability to be deposited in the respiratory tract in flu seasons - Ishmatov, Aleksandr N (PeerJ Preprints, 2016)
Marc Lipsitch and Cécile Viboud (2009) (Lipsitch and Viboud, 2009): “Seasonal variation in the incidence of communicable diseases is among the oldest observations in population biology, dating back at least to ancient Greece, yet our understanding of the mechanisms underlying this phenomenon remains hazy at best.” The latest researches show the infected people when breathing generate the infectious aerosols with particles below 1 µm. The airborne transmission of these particles is effective but the deposition of submicron particles in the respiratory tract (RT) has very low probability. Here I investigated the processes in RT when breathing cold air and its role in the delivery of viruses and bacteria of submicron and ultrafine sizes in RT. The original hypothesis of the highest probability of delivery and deposition of viruses or bacteria from inhaled air in the respiratory tract during flu seasons in different climatic conditions was investigated. On the basis of estimation I have originally shown: Breathing cool air leads to the supersaturation of air in RT; the air supersaturation leads to the intensive condensational growth(CG) of inhaled viruses or bacteria in RT; CG leads to the intensive and dramatically growth of deposition rate of viruses or bacteria in RT. Under normal conditions of inhaled air (T>20˚C; RH=60%) there is no transition in oversaturated condition in RT (CG is insignificant and probability of virus deposition on epithelium of RT is low – no more than 20%). But with an increase in RH of inhaled air the oversaturation in RT occurs even at warm temperature of inhaled air. For inhaled air of T=20°C, RH>70% the local supersaturation in the airways occurs: the concentration of liquid water in the mixed air in RT (СLiq) is СLiq<2·4g/kg and for T=25°C; RH>90% СLiq<1·2g/kg. The estimation also shown that for conditions of breathing cold air of T [-15..+15]˚C and Relatively Humidity (RH) of [30..60]% the supersaturation in the airways occurs: the concentration of liquid water in the mixed air in RT (СLiq) is [0·2..12·1]g/kg. Under these conditions the growth of inhaled particles by condensation in RT is significant. It lead to the dramatically growth of deposition rate of the viruses and bacteria in RT (up to 97%). These results correspond to influenza and seasonal respiratory infections in temperate and tropical climates and indicate the high probability of virus deposition on epithelium of RT. It may be the key to ‘the age-old epidemiologic mystery of influenza seasonality in the different climatic conditions’.
Keywords: airway; seasonality; respiratory infections; influenza; public health; epidemiology; flu season